Chinese Anesthesiologists Have High Burnout and Low Job Satisfaction: A Cross-Sectional Survey. (March 2018) - Li, Hange; Zuo, Mingzhang; Gelb, Adrian W.; Zhang, Biao; Zhao, Xiaohui; Yao, Dongdong; Xia, Di; Huang, Yuguang
Abstract : BACKGROUND: The Chinese health care system must meet the needs of 19% of the world's population. Despite recent economic growth, health care resources are unevenly distributed. This creates the potential for job stress and burnout. We therefore conducted a survey among anesthesiologists in the Beijing–Tianjin–Hebei region focusing on job satisfaction and burnout to determine the incidence and associated factors. METHODS: A large cross-sectional study was performed in the Beijing–Tianjin–Hebei region of China. The anonymous questionnaire was designed to collect and analyze the following information: (1) demographic characteristics and employer information; (2) job satisfaction assessed by Minnesota Satisfaction Questionnaire; (3) burnout assessed by Maslach Burnout Inventory-Human Service Survey; and (4) sleep pattern and physician–patient communication. RESULTS: Surveys were completed and returned from 211 hospitals (response rate 74%) and 2873 anesthesiologists (response rate 70%) during the period of June to August 2015. The overall job satisfaction score of Minnesota Satisfaction Questionnaire was 65.3 ± 11.5. Among the participants, 69% (95% confidence interval [CI], 67%–71%) met the criteria for burnout. The prevalence of high emotional exhaustion, high depersonalization, and low personal accomplishment was 57% (95% CI, 55%–59%), 49% (95% CI, 47%–51%), and 57% (95% CI, 55%–58%), respectively. Using multivariable logistic regression analysis, we found that age, hospital category, working hours per week, caseload per day, frequency of perceived challenging cases, income, and sleep quality were independent variables associated with burnout. Anesthesiologists with a high level of depersonalization tended to engage in shorter preoperative conversations with patients, provide less information about pain or the procedure, and to have less empathy with them. CONCLUSIONS: The anesthesiologists in the Beijing–Tianjin–Hebei region of China expressed a below-average level of job satisfaction, and suffered a significant degree of burnout. Improvement in job satisfaction and burnout might create a positive work climate that could benefit both the quality of patient care and the profession of anesthesiology in China.